Association between long-acting reversible contraceptive use, teenage pregnancy, and abortion rates in England - Connolly A; Pietri G; Yu J; Humphreys S (Dove Medical Press, 2014)
Anne Connolly,1 Guilhem Pietri,2 Jingbo Yu,3 Samantha Humphreys4 1The Ridge Medical Practice, Cousen Road, Bradford, UK; 2HERON – A PAREXEL® Company, London, UK; 3Merck & Co, Inc., Whitehouse Station, NJ, USA; 4Merck Sharp & Dohme Limited, Hertfordshire, UK Background: Since the late 1990s, the British government has launched major strategies to address high teenage pregnancy and abortion rates in England. These have focused in part on improving access to contraception through national campaigns. This study assessed teenage pregnancy and abortion rate trends since 1998 and possible associations with usage of long-acting reversible contraceptives (LARCs). Methods: Teenage conception rates and age-specific abortion rates were obtained from the Office for National Statistics and the Department of Health. LARC usage data was obtained for Depo-Provera, Implanon/Nexplanon, intrauterine devices, Mirena, and Noristerat from the IMS British Pharmaceutical Index, IMS Hospital Pharmacy Audit, IMS Disease Analyzer, and KT-31 reports. Through linear regression methods, changes in conception and abortion-related outcomes during 1998–2011 and the associations with LARC usage were assessed. Results: Conception rates for girls younger than 18 years of age decreased significantly between 1998–2011, from 46.6 to 30.7 per 1,000 girls. A statistically significant association was observed between this decrease and increased LARC usage (P=0.0024) in this population. Abortion rates among females aged <18 years or aged 18–19 years decreased between 1998–2011, and their associations with increased LARC usage were statistically significant (P=0.0029 and P=0.0479, respectively). The pattern in older women was complex; abortion rates in women aged 20–24 years or 25–34 years increased slightly from 1998 to 2011, with stabilization during 2007–2011. Conclusion: Increased LARC usage in England was significantly associated with decreased teenage pregnancy rates and abortion rates in females aged ,20 years. Government strategies appears to have a positive impact on these outcomes; however, abortion rates among women over 20 years of age remain an issue. Keywords: teenage pregnancy, abortion, long-acting reversible contraceptive, LARC